Copulation length on ovulatory and pregnancy rate in alpacas - Urviola Sánchez, Jesús Martín (2021)
An experiment was carried out at the Experimental Center La Raya-Universidad Nacional del Altiplano Puno, to determine the effect of copulation duration on ovulation and pregnancy in alpacas. 47 adult females were used (postpartum time ≥ 20 days and presence of a follicle ≥ 7 mm) distributed in three groups, according to copulation time: 20, 35 and 50 min, for G1 (n = 15), G2 (n = 16) and G3 (n = 16), respectively. For the mating, 6 reproducers of proven fertility were used, interrupting the copulation at the established time. Ovulation and pregnancy rates were evaluated on days 7 and 30 post service respectively (by ultrasound and receptivity of the female), the data were analyzed using X2 and simple correspondence. Both the ovulation rate (G1: 73.33%, G2: 81.25% and G3: 81.25%); and pregnancy (G1: 53.33%, G2: 81.25% and G3: 75%) were not different (P> 0.05). Pregnancy rates between G1 and G2 tended to be different (P <0.10), consistent with the simple correspondence analysis. Despite there being no differences in ovulation and pregnancy rates, there was a higher percentage trend in G2 and G3, suggesting that the longer duration of mating would have some positive effect on them, according to the simple correspondence analysis, and the trend of low significance (P <0.10) in favor of pregnancy in G2 compared to G1. In conclusion, there were no significant differences in the effect of copulation duration on ovulation; however, there was a 90% trend for the difference between mating duration of 35 minutes versus 20 minutes (in pregnancy).